Impact of corona discharge on Serratia marcescens and Pseudomonas syringae inactivation - Nedybaliuk, O.A.; Kot, N.S.; Kharina, A.V.; Fedirchyk, I.I. (Вопросы атомной науки и техники, 2021)
This work investigates the influence of corona discharge working in different treatment modes on the Serratia marcescens and Pseudomonas syringae bacteria cultures. The current-voltage characteristics of the discharge were measured in the 4…50 μA current range. The typical current and voltage oscillograms of corona discharge were measured when the pin’s point was near the water surface. Several treatment modes were discovered, which allowed to destroy or decrease the quantity of Serratia marcescens and Pseudomonas syringae bacteria by several orders of magnitude using 0.3 W corona discharge. The absorption spectra of the distilled water treated by the corona discharge were measured.